2022
DOI: 10.3390/su14031792
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Energy Management and Load Scheduling with Renewable Energy Integration in Smart Grid

Abstract: With the smart grid development, the modern electricity market is reformatted, where residential consumers can actively participate in the demand response (DR) program to balance demand with generation. However, lack of user knowledge is a challenging issue in responding to DR incentive signals. Thus, an Energy Management Controller (EMC) emerged that automatically respond to DR signal and solve energy management problem. On this note, in this work, a hybrid algorithm of Enhanced Differential Evolution (EDE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…In contrast to Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022), it was found that Smart Grid mainly depends on government governance, which includes both infrastructure support, and regulation of the energy economy. The role of corporate governance is secondary.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022), it was found that Smart Grid mainly depends on government governance, which includes both infrastructure support, and regulation of the energy economy. The role of corporate governance is secondary.…”
Section: Discussionmentioning
confidence: 96%
“…The publications of Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022) suggest the functioning and development of Smart Grid based on corporate governance with a secondary role of the state. Smart Grid is interpreted as a high-tech innovation of energy companies.…”
Section: Smart Grid As a Vector Of Energy Economy Developmentmentioning
confidence: 99%
“…Similarly, in [48], authors developed an optimal scheduling scheme for home appliances' power usage pattern management to mitigate PAR and alleviate appliances' waiting time. However, carbon emission and energy cost minimization is ignored.…”
Section: Stochastic Techniquesmentioning
confidence: 99%
“…In [50], the authors introduced Grey Wolf Accretive Satisfaction Algorithm for DSM to ensure the lowest energy cost and highest user comfort. A Candidate Solution Updating Algorithm (CSUA) is introduced in [48]. The purpose is to minimize PAR and appliance waiting time subjected to the desired user comfort level.…”
Section: Stochastic Techniquesmentioning
confidence: 99%
“…To encourage consumers, a real-time pricing (RTP) and demand response (DR) program are mathematically modelled and implemented to solve energy management problems via scheduling residential loads. To solve the energy management problem, a hybrid algorithm using an enhanced differential evolution (EDE) and a genetic algorithm (GA) were used by the authors of [32]. Luis Corona et al [33] presented a model to build and identify the main drivers of price convergence in Central-Western Europe (CWE) after applying the complex flow-based market coupling (FBMC) mechanism based on publicly available data.…”
Section: Introductionmentioning
confidence: 99%